Effect of CNT-Based Resin Modification on the Mechanical Properties of Polymer Composites - Nayak, Suhas Yeshwant; Shenoy, Satish; Hameed Sultan, Mohamed Thariq; Kini, Chandrakant R.; Seth, Aashna; Prabhu, Shrinivasa; Safri, Syafiqah Nur Azrie (Frontiers in Materials, 2021)
In this study an attempt is made to explore the possibility of substituting 3D E-glass fabric with eco-friendly basalt fabric along with modification of resin using MWCNTs, a material system about which very limited information exists. The study involves comparing the mechanical properties of two sets of composites. The first set comprised of 3D orthogonally woven E-glass reinforced epoxy composites, basalt reinforced epoxy composites and hybrid 3D E-glass orthogonally woven/ basalt reinforced epoxy composites while the second set of composites were same as the first but prepared with resin modified with Multi Walled Carbon Nanotubes (MWCNTs). All the composites were fabricated by hand lay-up and compression moulding techniques. To modify the resin for the second set of composites, MWCNTs were dispersed into the epoxy resin with acetone as a surfactant by magnetic stirring and ultra-sonification. Mechanical tests included tensile, flexural, and low velocity impact strength which were evaluated as per standards. Scanning Electron Microscopy (SEM) was employed to study the fractured surfaces. Results showed that resin modification didn’t yield any positive results on the mechanical properties of the composites. The highest tensile (364.4 MPa) and flexural strength (345.3 MPa) was obtained for 3D E-glass composites followed by basalt composites and hybrid 3D E-glass/ basalt composites while highest impact strength of 198.42 kJ/ m2 was exhibited by hybrid 3D E-glass/ basalt composites. SEM micrographs showed de-bonding between the modified matrix and fiber which was seen as one of the primary causes for relatively poor performance of composites prepared with modified resin. Fiber breakage, matrix cracking, fiber pull-out and delamination were the other modes of failure. Results suggest that hybridization with basalt fibers is much safe, cost effective and eco-friendly option over resin modification.